How Students Understand and Learn IMRAD Structure: Evidence from a Scientific Writing Workshop - Wanda Khairun Nasirin (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
This study aims to examine how undergraduate students understand and improve their knowledge of IMRAD-based scientific writing following a basic scientific writing workshop. The research adopts a descriptive quantitative approach using a pre-test and post-test design involving students from the Management Study Program, Faculty of Economics and Business, Universitas Teuku Umar (n=41), with 28 participants completing the pre-test and 26 completing the post-test. Data were analyzed descriptively to compare patterns of understanding before and after the workshop. The findings indicate that students initially demonstrated a basic understanding of IMRAD components, but showed limitations in higher-order conceptual aspects, particularly in distinguishing between Results and Discussion and understanding methodological rigor, as reflected by only 78.6% accuracy in identifying the Results section. Post-test results reveal a substantial improvement, with most students able to correctly identify structural errors, evaluate methodological transparency, and recognize issues such as overclaiming, redundancy, and poor logical flow, indicating a shift toward more analytical and critical thinking. However, the study is limited by the respondent gap between pre-test and post-test, which restricts individual-level comparison. Practically, the findings suggest that workshop-based learning is effective in strengthening academic writing skills, particularly when emphasizing conceptual clarity and applied analysis. Socially, improving students’ scientific writing competence may contribute to fostering a culture of scientific literacy and research engagement in higher education. This study provides empirical evidence on the progression of students’ understanding of IMRAD, highlighting the role of structured workshops in transforming misconceptions into analytical competence and offering insights for designing effective academic writing interventions.